The dynamics of a therophytic community in relation to self-regulation, herbivores and environmental variation - Acosta, F. J.; López, F.; Serrano, J. M. (Vegetatio, 1992)
The dynamics of a therophytic plant community in Central Spain has been studied, taking into account endogenous and exogenous factors. Using a simplified descriptive resolution a multi-species grass community and four canopy density types have been described in permanent quadrats. Transition matrices expressing the changes of vegetation state have been constructed. The importance of self- regulation was shown by the dependence of successive transitions on each other (highly significative log-linear models). The functioning cannot however be explained through a strict Markovian model because the transition probabilities are not stationary. The external local factors tested (microtopography, compactness and granivory) do not have a consistent effect on the vegetation dynamics, being variable over years, implying the importance of other more general factors on vegetation dynamics. Making transition probabilities dependent on external environmental factors rep
Keywords: Ants; Environmental influence; Granivory; Grasses; Markovian models; Vegetation dynamics